Migrants' religious spaces and the power of Christian Saints - the Latin American Virgin of Cisne in Spain - Eva Youkhana (University of Bonn, Center for Development Research (ZEF), 2016)
Religious institutions such as the Catholic Church are gaining in importance again in the wake of the economic crisis in Spain. They act as a reference point and meeting place which keep the faith community together. Tangible assistance is offered and transnational communication structures and family bonds are sustained. With its patron saints, the Catholic Church serves as a place of remembrance to produce and reproduce senses of belongings that date back to the early colonial era. Social relations of migrants are manifested in a space which symbolizes the power and glory of the former Colonial regime. Taking the example of the congregation of San Lorenzo in an immigration neighbourhood in Madrid, I discuss the role and agency of religious artefacts in re-producing collective identities and allocating social and financial resources. By focusing on the object itself, the functions and cultural meanings of the figure in different historical contexts become apparent. The religious staging around the object of the saint show spatially and chronologically comprehensive chains of interaction which reflect deep seated power relations between the immigrant and the host communities.
Keywords: 330; transnational religious spaces; agency of objects; colonization; politics of belonging; Madrid